Design, Computational Evaluation and Route of Synthesis Validation of New JAK2 Inhibitors to Treat Inflammatory Diseases - Jarukorn Pornsupawat; M. Paul Gleeson (My University, 2025)
In this research we report the design of new JAK2 inhibitors using structure-based and ligand-based design approaches. Novel JAK2 inhibitors were designed containing biostatic modifications developed from related scaffolds. The JAK2 binding characteristics were studied using molecular docking and an assessment of their overall drug likeness was made though the prediction of key physical properties. Validation of routes of synthesis have been undertaken to assess the feasibility of preparing the compounds. Our results suggest that the new molecules have desirable physical properties and are highly likely to be inhibitors of JAK2 kinase. In addition, we have validated the synthetic conditions and intermediates needed for their preparation by preparing 4 key exemplars.
Keywords: Cytokine Signaling Pathways and Interactions; Tuberculosis Research and Epidemiology; Myeloproliferative Neoplasms: Diagnosis and Treatment